Tactical and technical indicators of boxers with different fighting styles - Demchenko, Yu. V.; Golovlev, V. A.; Yatsin, Y. V.; Salnikov, V. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the characteristics of striking actions in accordance with individual styles of fighting with special training.